2018
DOI: 10.1371/journal.pone.0202228
|View full text |Cite|
|
Sign up to set email alerts
|

Motor planning error in Parkinson's disease and its clinical correlates

Abstract: This study aimed to investigate (a) motor planning difficulty by using a two-step test in Parkinson’s disease (PD) compared with age-matched healthy subjects and (b) the relationship between motor planning difficulty and clinical factors. The two-step test was performed by 58 patients with PD with Hoehn & Yahr (H&Y) stage I–IV and 110 age-matched healthy older adult controls. In the two-step test, the participants estimated the two-step distance with maximum effort. Subsequently, they performed the actual two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…In other words, the overestimation was associated with higher PD severity. Similar to the present study, Kawasaki et al [ 11 ] measured the estimation error distance using a two-step test in PD patients and performed a correlation analysis between the estimation error distance and H&Y. They found no correlation between the estimation error distance and H & Y; however, in this study, we observed a positive correlation.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In other words, the overestimation was associated with higher PD severity. Similar to the present study, Kawasaki et al [ 11 ] measured the estimation error distance using a two-step test in PD patients and performed a correlation analysis between the estimation error distance and H&Y. They found no correlation between the estimation error distance and H & Y; however, in this study, we observed a positive correlation.…”
Section: Discussionsupporting
confidence: 82%
“…They found no correlation between the estimation error distance and H & Y; however, in this study, we observed a positive correlation. Our study targeted more severe PD patients than the previous studies (H & Y: 3.11 ± 0.67, present study; 2.91 ± 0.70 and 2.50 ± 0.70, previous studies) [ 11 ]. H & Y signifies the severity of the motor function deficit in PD patients.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Regarding individuals' estimation errors, it has been reported that for healthy elderly individuals and patients suffering from Parkinson's disease, dissociation of motor imagery and execution time is related to physical functions 17,25) . However, the results showed no correlation between estimation error and physical functions.…”
Section: Discussionmentioning
confidence: 99%